Institutional experience, formal institutional quality, and firm performance: An analysis of firms from the European Union - Alexandre Oliveira; Fernando Manuel Pereira Oliveira Carvalho; Nuno Rosa Reis (BRQ Business Research Quarterly, 2025)
Firms' success depends on their ability to deal with formal institutional quality. Specifically, firms exposed to a diversified set of institutional profiles can achieve institutional competitive advantage that provides firms with diverse knowledge and broader learning opportunities. While prior studies argued that being exposed to a diversified set of institutional profiles negatively influences firms because institutional knowledge can only be replicated in similar institutional profiles, they missed the point of learning from diversity. The purpose of this study is to further understand how firms' institutional experience moderates the relationship between formal institutional quality and firms' performance. We argue that firms with higher and more diverse institutional experience will adapt more efficiently to formal institutional quality, thus improving firms' performance. We test the hypotheses on 4,011 publicly traded firms from the European Union between 2010 and 2021, and our results show that firms that develop higher institutional experience are better able to efficiently adapt to and leverage formal institutional quality and achieve higher firm performance. We contribute to the ongoing discussion on how formal institutions influence firms' performance by acknowledging the importance of developing a diversified institutional experience.
Keywords: F23; 650; Formal institutional quality; firms' performance; institutional diversity; institutional experience; European Union